Kumpulan cerpen parasit dan sesudah perang - Anwar Ridhwan (Dewan Bahasa dan Pustaka, 2019)
The collection of short stories "Parasit dan Sesudah Perang" contains 22 early short stories of the Sasterawan Negara Anwar Ridhwan that he produced during the first decade of his authorship. This collection of short stories is the latest edition of his collection of short stories "Parasit" published in 1976 (DBP), and "Sesudah Perang" published in 1978 (DBP). "Parasit dan Sesudah Perang" is not only a dramatic depiction of the story of life and humanity as well as suffering, but also an examination and thoughts of Anwar Ridhwan on the events happening around him. The author brings diverse and interesting themes and is helped by a fresh and imaginative style of language through his short stories.